Lithium treatment and hippocampal subfields and amygdala volumes in bipolar disorder. (24th March 2015) - Hartberg, Cecilie Bhandari; Jørgensen, Kjetil Nordbø; Haukvik, Unn Kristin; Westlye, Lars Tjelta; Melle, Ingrid; Andreassen, Ole Andreas; Agartz, Ingrid
<x xml:space="preserve">Abstract</x> Objectives Results from magnetic resonance imaging (MRI) studies are heterogeneous with regard to hippocampal and amygdala volume alterations in bipolar disorder (BD). Lithium treatment may influence both structures. It is unknown if lithium treatment has distinct effects on hippocampal subfield volumes and if subfield volumes change over the course of illness in BD. Methods MRI scans were obtained for 34 lithium‐treated patients with BD (Li+), 147 patients with BD who were not treated with lithium (Non‐Li), and 300 healthy controls. Hippocampal total and subfield volumes and amygdala volumes were automatically estimated using Freesurfer. General linear models were used to investigate volume differences between groups and the effects of illness course and lithium treatment. Results The Non‐Li BD group displayed significantly smaller bilateral cornu ammonis (CA) 2/3 and CA4/dentate gyrus (DG) subfields, total hippocampal volumes, right CA1 and right subiculum subfields, and left amygdala volume compared to healthy controls. There were no differences between the Li+ BD and either the Non‐Li BD or the healthy control groups. In patients with numerous affective episodes, Non‐Li BD patients had smaller left CA1 and CA2/3 volumes compared to Li+ BD patients and healthy controls. There were positive associations between lithium treatment duration and left amygdala volume. Conclusions Hippocampal subfield and amygdala volumes were reduced in Non‐Li BD patients compared to healthy controls, whereas the Li+ BD volumes were no different from those in Non‐Li BD patients or healthy controls. Over the course of BD, lithium treatment might counteract reductions specifically in the left CA1 and CA2/3 hippocampal subfields and amygdala volumes, in accordance with the suggested neuroprotective effects of lithium.